CONCEPTUAL APPROACHES TO DETERMINING THE ESSENCE OF THE MOTIVATION OF BANK LENDING OF AGRICULTURAL GOODS PRODUCERS AND JUSTIFICATION OF THE CONTENT OF ITS MECHANISM - Boiarko, Iryna; Sydorova, Olena (Socio-economic relations in the digital society, 2023)
Thanks to the use of a wide range of scientific methods, the article highlights conceptual approaches to understanding the essence of the motivation of bank lending to agricultural producers through the prism of clarifying the concept of "motivation". The scientific approaches of domestic and foreign researchers to understanding the content of motivation are summarized, which made it possible to distinguish scientific currents according to homogeneous groups of features. Clarification of the content of the concept "mechanism of motivation for bank lending to agricultural producers" contributed to the formation of the organizational and functional set of its elements and the disclosure of the relationships between them.The paper determined that the mechanism of motivation for bank lending to agricultural producers can be a complex set of elements, namely: a) factors of economic activity of banks; b) an ordered set of types of motivators, which includes external (macroeconomic) factors (state, market, social), internal motivators of the bank (microeconomic factors) and self-motivation (nanoeconomic factors), as well as hierarchical relationships between them.The article examines the evolution of the use of various forms of motivational tools to support agricultural commodity producers, reveals the specifics of their crediting and the mechanism of providing loans to agricultural commodity producers.On the basis of the generalization of scientific developments, the list of functions and principles of motivation of bank crediting of agricultural commodity producers has been specified, as well as the corresponding functions and principles of the mechanism of such motivation have been highlighted.The generalization of scientific approaches to the interpretation of the mechanism of motivation for bank lending to agricultural producers made it possible to single out the conditions for its construction, as well as specify the exogenous and endogenous factors that affect the change in the bank's motivators.A review of the global experience of motivating bank crediting of agricultural producers made it possible to single out the main tools contributing to its activation.
Keywords: motivation; motivational mechanism; bank lending; agricultural commodity producers; mechanism of motivation for bank lending to agricultural commodity producers